Australian Mathematics Literacy Perspectives: Assessment - Allan Leslie White (SEAMEO Regional Centre for QITEP in Mathematics, 2018)
This is a companion paper and should be read with the earlier one (White, 2017) that focused mainly on Australian governmental policies. In this paper, a more classroom and student focus will be adopted while summarising a few of the salient points of the first paper. A brief listing of five different types of mathematical literacy is provided. The definition used by the Program for International Student Assessment (PISA) is selected andsome brief remarks are provided on this program. PISA items are presented in the form of word problems. If a country such as Australia or Indonesia wants to improve their PISA results then it would demand that some class time is devoted to the development of the abilities of younger students to handle word problems before they turn fifteen and are subjected to PISA. To support classroom teachers, Newman (1977, 1983) defined five specific mathematical literacy levels as crucial to performance on mathematical wordproblems: reading, comprehension, transformation, process skills, and encoding. Newman's Error Analysis (NEA) provides a framework for considering the reasons that underlay the difficulties students experience with mathematical word problems and a process that assists teachers to determine where misunderstandings occur. NEA also provides directions for where teachers could target effective teaching strategies to overcome them. There is a brief discussion of strategies to assist students improve theirmathematical literacy.